2020
DOI: 10.1371/journal.pone.0242382
|View full text |Cite
|
Sign up to set email alerts
|

Molecular assessment and transcriptome profiling of wild fish populations of Oryzias mekongensis and O. songkhramensis (Adrianichthyidae: Beloniformes) from Thailand

Abstract: Among the fish of the genus Oryzias, two species are frequently used as model animals in biological research. In Thailand, Oryzias mekongensis is usually found in natural freshwater near the Mekong Basin in the northeast region, while O. songkhramensis inhabits the Songkhram Basin. For differential morphological identification, the coloured bands on the dorsal and ventral margins of the caudal fin are used to distinguish O. mekongensis from O. songkhramensis. However, these characteristics are insufficient to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…In Thailand, Thai ricefish populations have been mainly separated into two groups based on the COI gene and displacement (D) loops (Ngamniyom et al, 2020). Recently, Ngamniyom (2020) reported that the population diversity of O. mekongensis and O. songkhramensis associated with river positions in northeastern Thailand. The Gulf of Thailand and the Andaman Sea of Thailand are physical barriers separated by the Thai-Malaysian Peninsula (Mahidol et al, 2007;Phinchongsakuldit et al, 2013;Sheldon et al, 2015;Lange et al, 2019), where the geographical pattern includes long mountain and hill ranges that were also taken into the account (Gupta, 2005;Wolf et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, Thai ricefish populations have been mainly separated into two groups based on the COI gene and displacement (D) loops (Ngamniyom et al, 2020). Recently, Ngamniyom (2020) reported that the population diversity of O. mekongensis and O. songkhramensis associated with river positions in northeastern Thailand. The Gulf of Thailand and the Andaman Sea of Thailand are physical barriers separated by the Thai-Malaysian Peninsula (Mahidol et al, 2007;Phinchongsakuldit et al, 2013;Sheldon et al, 2015;Lange et al, 2019), where the geographical pattern includes long mountain and hill ranges that were also taken into the account (Gupta, 2005;Wolf et al, 2020).…”
Section: Discussionmentioning
confidence: 99%